The Relationship between Hearing Thresholds Estimation and Results of Auditory-Verbal Therapy in Children with Bilateral Congenital Severe to Profound Sensorineural Hearing Loss. - sadegh jafarzadeh (Shiraz University of Medical Sciences, 2021)
Background: congenital severe to profound sensorineural hearing loss (SP-SNHL) causes serious difficulties in production and comprehension of speech, necessitates use of a thorough rehabilitation program at early age. The aim of this study was to evaluate the relationship between hearing thresholds and the result of auditory rehabilitation in children with bilateral congenital SP-SNHL.   Methods: This is a retrospective study. Thirty-five children (23 males and 12 females) with bilateral congenital SP-SNHL were evaluated based on Auditory Steady-State Response (ASSR). The mean age of children at the beginning of rehabilitation was 37.36 (±17.10) months. They received bilateral superpower hearing aids and auditory rehabilitation based on Auditory-Verbal Therapy (AVT) approach. Their Speech production and comprehension were assessed at the beginning and end of rehabilitation via Speech Intelligibility Rating (SIR) and Categories of Auditory Performance (CAP). Results: The SIR and CAP scores showed improvement in 12 (34.3%) and 25 (71.4%) children, respectively. These children had lower ASSR thresholds in 0.5 to 4 k Hz relative to others. The mean ASSR thresholds were 85.63 to 97.50 versus 96.09 to 104.75 (p < 0.05). Also, lower hearing thresholds were related to better results in auditory rehabilitation (p < 0.05). Conclusion: Lower hearing thresholds in children with SP-SNHL are associated with better rehabilitation results.